2017
DOI: 10.1088/1757-899x/163/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal analysis of the internal combustion engine piston using Ansys

Abstract: In engines pistons are very important parts to produce power. Piston fail mainly due to mechanical stresses and thermal stresses. An analysis of thermal stress and damages due to application of temperature is presented and analysed in this work. Aluminium alloy have been selected for thermal analysis of piston. Results are shown and a comparison is made to find the most suited design Analysis of piston crown is done with boundary conditions, which includes pressure on piston head during working condition and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
3
3
0
Order By: Relevance
“…5 for dome and flat shape faced piston failures. The same results were achieved by other researchers [7,9,11] revealing similarly effective stress zones on the piston edges during simulations. The fatigue life results show that the thermo-mechanical fatigue life decreases with increasing mechanical loading for the circular cut section of the top face of the piston shown in Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…5 for dome and flat shape faced piston failures. The same results were achieved by other researchers [7,9,11] revealing similarly effective stress zones on the piston edges during simulations. The fatigue life results show that the thermo-mechanical fatigue life decreases with increasing mechanical loading for the circular cut section of the top face of the piston shown in Fig.…”
Section: Resultssupporting
confidence: 89%
“…6. Similarly, other researchers [7,9,11] reported that the effective stress occurred at the top surface and edges of the piston. According to the presented analysis, thermo-mechanical fatigue loading limit depends on the selected type of material and is very close to 5MPa , where the highest compression ratio in the IC engine produces a pressure of about 3 to 4 MPa at the end of compression stroke [15].…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Silicon based aluminum alloy was regarded as the material for the piston. Eutectic alloy (ATC12CuMgNi) which is the material of the piston, its material properties have been listed in table 1 (V G Cioată et al, 2017). CAD file of the piston was produced with the help of Solidworks 2017 as shown in Figure 7.…”
Section: Design Datamentioning
confidence: 99%
“…Power of the IC engine is limited by the resistance offered by mechanical and thermal force acting on the piston. Therefore design of the piston is very important, as it would define the load and stress on the piston (V G Cioată et al, 2017). As diesel and waste cooking oil biodiesel have similar properties, they can be used in the same compression ignition engine.…”
Section: Introductionmentioning
confidence: 99%